(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
Cocuy de penca is an indigenous alcoholic beverage of the Venezuelan territory, produced from the Agave Cocui Trelease plant and considered as natural, ancestral and cultural heritage of the nation, being a distillate that has gained relevance in the market in recent years due to their particular sensory characteristics. The purpose of the research was to establish the organoleptic properties of the Cocuy de Penca produced in Lara. For this, eight samples from different parishes were selected; subsequently, the study had the following order: definition of the sensory descriptors, construction of the survey, selection of the panel of juries, conditioning of the environment for the tasting, preparation of the samples and, finally, sensory analysis. Obtaining that the organoleptic profile of the samples of Cocuy larense make it up two descriptors for visual analysis, twenty for olfactory and eighteen for gustatory.